Links in the Micropolitical Networks That Determine Teaching Practice in Secondary Education Teachers (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research explains how secondary school teachers, through their actions, articulate connections that allow them to lend representativeness to their ideological discourses within the established framework, thus giving rise to the expression of group identity. A qualitative approach, using an ethnographic design, is employed to explore, examine, and understand the intersubjective links within the school organization and to produce profound interpretations and cultural meanings from the participants' perspectives. The information is gathered using semi-structured techniques, such as participant observation and interviews, as an approach to the interactions between teachers that constitute their daily performance, which then becomes an object of study. The starting point is that group dynamics act as a filter for ideology, because they go beyond simply being a group, incorporating the production expressed in its cohesion and fragmentation. The concluding argument is that connection as an institutional bond configures a habitus that generates a structure of collective behavior from which teaching practice emerges, established in the bonds of connection with the groups from which education is instituted.